Pemodelan dan Identifikasi Sumberdaya Nikel Laterit dengan Metode Spasi Blok dan Pengaruhnya terhadap Spasi Bor - Al Amin Siharis (LP3M Universitas Muhammadiyah Kendari, 2022)
Mineral resource estimation is strongly influenced by the density of drill point data. Where, the closer of the drill point distance exhibits the high accuracy the estimation identification of nickel laterite and vice versa. Meanwhile, the sparser of the drill point distance shows the low accuracy estimation results. in where, the accuracy is expressed as a standard error or error value determination over data calculated. In this study, the estimation method was applied by using nearest neighborhood point (NNP) method for 2 variations data. First data was explored with a drill spacing of 25 m and the second data was evaluated with a drill spacing of 50 m. Based on these results via NNP method under estimation software was provided the different amount of nickel laterite resources for each type data. The drill spacing of 25 m has showed of 1,008,094 tons, while the drill spacing for 50 m has exhibited of 1,048,281 tons. The error value over drill spacing of 25 m is 0.02, while for 50 m is 0.03, respectively. These results can be concluded that the data with lower density, although it produces more nickel resources, but in terms of accuracy identification has a low-level accuracy